Clinical outcomes after online adaptive MR-guided stereotactic body radiotherapy for pancreatic tumors on a 1.5 T MR-linac - Eijkelenkamp, Hidde; Grimbergen, Guus; Daamen, Lois A.; Heerkens, Hanne D.; van de Ven, Saskia; Mook, Stella; Meijer, Gert J.; Molenaar, Izaak Q.; van Santvoort, Hjalmar C.; Paulson, Eric; Erickson, Beth Ann; Verkooijen, Helena M.; et al. (Frontiers in Oncology, 2023)
Online adaptive MR-guided radiotherapy (MRgRT) is a promising treatment modality for pancreatic cancer and is being employed by an increasing number of centers worldwide. However, clinical outcomes have only been reported on a small scale, often from single institutes and in the context of clinical trials, in which strict patient selection might limit generalizability of outcomes. This study presents clinical outcomes of a large, international cohort of patients with (peri)pancreatic tumors treated with online adaptive MRgRT.We evaluated clinical outcomes and treatment details of patients with (peri)pancreatic tumors treated on a 1.5 Tesla (T) MR-linac in two large volume treatment centers participating in the prospective MOMENTUM cohort (NCT04075305). Treatments were evaluated through schematics, dosage, delivery strategies and success rates. Acute toxicity was assessed until three months after MRgRT started, and late toxicity from three to twelve months follow-up (FU). The EORTC QLQ-C30 questionnaire was used to evaluate the quality of life (QoL) at baseline and three months FU. Furthermore, we used the Kaplan-Meier analysis to calculate the cumulative overall survival.Results: A total of 80 patients were assessed with a median FU of 8 months (range 1 to 39 months). Thirty-four patients had an unresectable primary tumor or were medically inoperable, 29 had an isolated local recurrence, and seventeen had an oligometastasis. 357 of the 358 fractions from all hypofractionated schemes were delivered as planned. Grade 3-4 acute toxicity occurred in 3 of 59 patients (5%) with hypofractionated MRgRT, and grade 3-4 late toxicity in 5 of 41 patients (12%). Six patients died within three months after MRgRT; in one of these patients, RT attribution could not be ruled out as cause of death. The QLQ-C30 global health status remained stable from baseline to three months FU (70.5 at baseline, median change of +2.7 [P = 0.5]). The one-year overall survival for the entire cohort was 67%, and for the primary tumor group 66%.Online adaptive MRgRT for (peri)pancreatic tumors on a 1.5 T MR-Linac could be delivered as planned, with low numbers of missed fractions. In addition, treatments were associated with limited grade 3-4 toxicity and stable QoL at three months FU.